Potential And Utilization Of Pangi Plant (Pangium Edule Reinw) In Agroforestry Land In Kalembang Village, Sangalla District, Tana Toraja Regency - Srigae Rantelimbong; Andi Irmayanti Idris (Jurnal Penelitian Kehutanan BONITA, 2023)
Pangi (Pangium edule Reinw) is a type of non-timber forest product commodity in the vegetable group, in which all parts of this plant can be utilized. Pangi plants are planted on agroforestry land so that they can be used sustainably to fulfill their subsistence needs. Some of the people of Kalembang Village cultivate their land by turning it into agroforestry land and planting seasonal crops, fruits and forestry plants. This study aims to describe the potential and utilization of pangi plants found in the agroforestry land of the Kalembang community, Sangalla' District, Tana Toraja Regency. Simple random sampling technique and interviews are the methods used in this study. The data obtained is arranged in tabular form and then described in a descriptive way to describe the use of Pangi by the community. The results showed that there were 4 hamlets in Kalembang Village, but this research was only conducted in Kalembang Hamlet. The area of agroforestry land in Kalembang Village is 325 ha, while the area planted by pangi is on average 0.25-1 ha with around 10-31 pangi trees. The research data in the field shows that there are 524 trees which are still productive in producing fruit or the equivalent of 90%, while the number of trees that are not productive in producing fruit (dead) is 58 trees or the equivalent of 10%. Respondents in Kalembang Village only used 4 products produced from pangi plants, namely (stems) used as building materials; (leaves) are used as wrappers for meat so they don't spoil quickly and leaves are easily used as vegetables; (pangi fruit/seeds) are used as food ingredients, namely vegetables and seasoning (Kluwek).